Design of A Web-Based Operational Management Information System for Playmania LPJ - Zahra Fahrani; Ahmad Ferdian Shobur (Universitas Malikussaleh, 2026)
In daily operational activities, Playmania Lippo Plaza Jambi has utilized a computerized system for sales transactions. However, inventory management, petty cash recording, and operational reporting are still managed separately using spreadsheet files, while children’s accident records are documented manually using paper forms. In addition, playtime monitoring is still supported by manual voice announcements through a microphone. These conditions result in inefficient data management and increase the risk of recording errors. This study aims to design and develop a web-based Operational Management Information System for Playmania LPJ using the Waterfall method. The system is developed to integrate sales transactions, inventory management, petty cash recording, incident reporting, and playtime monitoring within a single platform. The implementation process utilizes PHP and MySQL technologies, while system functionality is evaluated using Black Box Testing. The developed system consists of integrated modules for inventory management, customer management, sales transactions, petty cash recording, incident reporting, user management, and real-time playtime monitoring equipped with an automatic voice announcement feature. The test results indicate that all system functions operate according to the expected requirements and successfully support operational activities in a coordinated and efficient manner. Therefore, the proposed system is capable of improving the effectiveness and accuracy of operational data management, facilitating monitoring activities, accelerating report generation, and supporting decision-making processes at Playmania LPJ.